“Be In But Not Of” the University: Collective Refusal as Resistance to Isolation and Precarity - Henderson, Maya; Mandal, Sayantika; Prostine, Ben; Rice, Jennifer L.; Taillefer, Kayleigh; Trauger, Amy; Urresty-Vargas, Constanza; Wayson, Elizabeth (ACME, 2025)
Many of us in academia navigate a visceral tension: our role as learners, teachers, and employees allows us the refuge to do meaningful work and deep thinking on issues of importance, yet, this privilege comes amid long-standing and ongoing racialized exclusions and neoliberal rationalities of productivity in the academy. We explore, here, the role that collective refusal can play in this navigation. We describe ways that we can come together, even if our positionalities are different and our benefits uneven, to refuse the most oppressive aspects of higher education. We draw on various notions of refusal, largely rooted in Black and Indigenous scholarship, to identify both the harms of higher education and how “to be in but not of” (Harney and Moten 2013, 26) the university. This requires collective support of one another through acts of refusal in learning, knowledge production, and employment that allow us to have a shared stake in the reform of academic life.